PENGARUH DISIPLIN KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN DI LEMBAGA PERKREDITAN DESA (LPD) PADANGSAMBIAN - Anak Agung Ngurah Ryan Pratama Putra; Ni Luh Sili Antari; Ni Made Ernila Junipisa (Universitas Triatma Mulya, 2023)
Work discipline is a very important thing for organizational growth, especially used to motivate employees to discipline themselves in carrying out work both individually and in groups.and can also be done through changes to the Work Environment, so that it will produce employee performance according to what is expected by the leadership. This study aims to analyze the influence of work discipline with employee performance, the influence between the work environment and employee performance. The magnitude of the influence of work discipline and work environment with employee performance and independent variables that have a dominant influence on employee performance at the Padangsambian Village Credit Institution.The population of this study amounted to 35 people, the analysis tool used was Multiple Linear Regression Analysis. The hypothesis test used is t test to test the effect of work discipline on employee performance, and determination analysis to analyze the magnitude of the influence of the independent variable on the dependent variable. The regression equation obtained Y = 0.608 + 0.701 X1 + 0.257 X2 of this model shows that 1) there is a positive and significant influence of work discipline on employee performance.2) there is a positive and significant influence of the work environment on employee performance.3) the magnitude of the influence of work discipline and work environment on employee performance. Work discipline is an independent variable that has a dominant influence on employee performance at the Padangsambian Village Credit Institution.